Strengthening the Quality of Female Graduates Through Competency-Based Education Model in the Islamic Religious Education Program - Diana Sartika; Iswantir iswantir; Salmi wati Salmi wati; Sulasmi Sulasmi (Jurnal Pendidikan (Teori dan Praktik), 2025)
The Islamic Religious Education study program at Islamic Religious Universities (PTKI) has a crucial role in Islamic education and prepares competent graduates in the world of Education. For this reason, the PAI Study Program must be able to develop educational programs that can produce competent female students in the world of work. STIT Diniyyah Puteri is one of the Tarbiyyah Colleges of Science specifically for women, one of whose study programs is Islamic Religious Education (PAI). STIT Diniyyah Puteri has the goal of producing Trusted Techer. To produce teachers who are trusted teachers, STIT Diniyyah Puteri must have a program that can improve the competence of female students. To see what things are done by the PAI Study Program STIT Diniyyah Puteri in improving the competence of female students in order to produce teachers who are Trusted Teachers, this research was carried out. This research was carried out using a qualitative descriptive method using the observation method and using a literature study to support the observation results. There are ways that can be done by the Study Program by ensuring the implementation of learning carried out by lecturers is by using the student center model, improving the literacy skills of female students in lectures and maximizing internship programs for female students on a scheduled basis or observation in each course in the field